Eutectic mixture-functionalized carbon nanomaterials for selective amperometric detection of nitrite using modified glassy carbon electrode - Abo-Hamad, Ali; AlSaadi, Mohammed AbdulHakim; Hashim, Mohd Ali (Elsevier, 2018)
Choline chloride-urea (CU) (1:2 M ratio) was used to functionalize two types of carbon nanomaterials (CNMs); multiwall carbon nanotube (MWCNT) and graphene (Gr). A composite of both components was used to modify the surface of glassy carbon electrode (GCE) designated as (CU/MWCNT/Gr/GCE). CU-functionalized CNMs modified GCs have shown higher catalytic activity towards the oxidation of nitrite (NO2−) compared to bare and pristine CNM modified electrodes. However, the highest performance was found for a mixture of Gr and MWCNT (50% w/w). CU-functionalized CNMs were characterized by scanning electron microscope, Raman spectroscopy and X-ray diffraction. It has been hypothesized that covalent functionalization and exfoliation were responsible for the improvement in electrocatalytic activity of the modified electrode. CU/MWCNT/Gr/GCE presented a good stability, reproducibility with a detection limit 0.30 μM and a linear range between 5 μM–360 μM.